Efficient co‐production of propionic acid and succinic acid by Propionibacterium acidipropionici using membrane separation coupled technology. Issue 6 (7th June 2021) - Li, Xiaolian; Wei, Liquan; Wang, Ziqiang; Wang, Yunshan; Su, Zhiguo
Abstract: To improve the fermentation efficiency of Propionibacterium acidipropionici, a semi‐continuous coupled fermentation process was established to achieve co‐production of propionic acid (PA) and succinic acid (SA). First, the optimal proportion of glucose (Glc) and glycerol (Gl) as a mixed carbon source was determined, and the feeding procedure of Gl was optimized to make more energy flow in the direction of product synthesis. Then, ZGD630 anion exchange resin was used for efficient adsorption of PA, thereby eliminating the feedback inhibition effect of PA. Finally, an efficient, coupled fermentation process of P. acidipropionici characterized by membrane separation and chromatography technology was developed. The concentrations of PA and SA reached 62.22 ± 2.32 and 20.45 ± 1.34 g L −1, with corresponding productivity of 0.43 and 0.14 g L −1 h −1, increased by 65.38% and 48.54%, respectively. Membrane separation coupled fermentation of PA and SA could significantly improve the process economics of P. acidipropionici, and has good prospects for industrial application.